Coating method for improving ionic conductivity and air stability of lithium lanthanum zirconium oxide solid electrolyte

By coating lithium lanthanum zirconium oxygen material doped with tantalum element, the three-sintering process is used to improve the ionic conductivity and air stability of the lithium lanthanum zirconium oxygen solid electrolyte, solving its key problems in application and realizing More efficient preparation and stability, suitable for large-scale production.

CN119133581APending Publication Date: 2024-12-13GUANGDONG HENGYU ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411277012.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-12
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

Lithanum zirconium oxygen (LLZO) solid electrolytes face interfacial problems, air stability problems and insufficient ionic conductivity in applications. The existing technology is relatively low in stability and preparation efficiency, making it difficult to achieve large-scale production.

Method used

By coating lithium lanthanum zirconium oxygen material doped with lithium nitride to tantalum element, the three-sintering process is used to improve its ionic conductivity and air stability, including the first sintering to prepare the M-doped lithium lanthanum zirconium oxygen, the second Sub-low-temperature sintering is carried out for lithium nitride coating, and the third high-temperature sintering is used to press the electrolyte sheet.

Benefits of technology

显著提高了锂镧锆氧固态电解质的离子电导率和在干燥空气中的稳定性,减少了后续电芯制备的繁琐工序,降低了环境控制成本,提高了制备效率。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119133581A_ABST
    Figure CN119133581A_ABST
Patent Text Reader

Abstract

The invention discloses a coating method for improving the ionic conductivity and air stability of a lithium lanthanum zirconium oxide solid electrolyte, which comprises the following steps: step 1, preparing an M element doped lithium lanthanum zirconium oxide solid electrolyte by adopting first sintering at the sintering temperature of 900-1000 DEG C and the heat preservation time of 6 hours, and taking out the M element doped lithium lanthanum zirconium oxide solid electrolyte; crushing and sieving the prepared blocky material to obtain a granular material higher than 100 meshes, and drying and storing the granular material in a polypropylene bottle; 2, the granular material is subjected to secondary low-temperature sintering, the M-element lithium lanthanum zirconium oxide material is coated with lithium nitride, the adding proportion of the lithium nitride is 0 wt%-0.9 wt%, the sintering temperature is 850-900 DEG C, the heat preservation time is 4 h, and after secondary coating sintering, the M-element lithium lanthanum zirconium oxide material coated with the lithium nitride is obtained through crushing and screening of 100 meshes; and step 3, pressing the finally sintered material in the step 2 into an electrolyte sheet through an isostatic press, and then carrying out third high-temperature sintering at the sintering temperature of 1200-1300 DEG C for 40 minutes to finally obtain the finished electrolyte sheet.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of solid-state batteries, and in particular to a coating method for improving the ionic conductivity and air stability of a lithium lanthanum zirconium oxygen solid-state electrolyte. Background Art

[0002] Lithium lanthanum zirconium oxide (LLZO) solid electrolytes are considered key materials for solid-state batteries in next-generation energy storage technologies due to their high safety, high energy density, and long life. However, the application of LLZO-based solid-state batteries faces challenges such as interface issues, air stability, and ionic conductivity.

[0003] Of course, the existing Chinese invention patent CN201910786814.5 improves the solid electrolyte ion conductivity, mechanical properties, thermal stability and compatibility with positive and negative electrodes through multi-layer composite solid electrolytes.

[0004] However, this structure has low stability and preparation efficiency during actual production, making it difficult to achieve large-scale production and processing. Summary of the Invention

[0005] The main purpose of the present invention is to propose a coating method for improving the ionic conductivity and air stability of lithium lanthanum zirconium oxide solid electrolytes. By coating lithium nitride (lithium ion conductor) on tantalum-doped lithium lanthanum zirconium oxide materials, its ionic conductivity and stability in dry air can be improved, which reduces the environmental control cost and improves the efficiency of mass production of tantalum-doped lithium lanthanum zirconium oxide materials.

[0006] To achieve the above objectives, the present invention proposes a coating method for improving the ionic conductivity and air stability of lithium lanthanum zirconium oxide solid electrolyte, comprising:

[0007] Step 1: Prepare M-doped lithium lanthanum zirconium oxide solid electrolyte (LLZO) by first sintering at a temperature of 900-1000°C for 6 hours. The obtained bulk material is crushed and sieved to obtain granular material with a size larger than 100 mesh, which is then placed in a polypropylene bottle for drying and storage.

[0008] The general chemical formula of the lithium lanthanum zirconium oxide solid electrolyte is: LixLa3Zr2-yMyO12, wherein 4≤x≤7, 0≤y≤0.6

[0009] Step 2: The granular material is subjected to a second low-temperature sintering to obtain a lithium nitride-coated lithium lanthanum zirconium oxide material of the M element, wherein the addition ratio of the lithium nitride is 0wt%-0.9wt%, the sintering temperature is 850-900°C, and the holding time is 4h. After the secondary coating and sintering, the lithium lanthanum zirconium oxide material of the M element coated with lithium nitride is obtained by crushing and screening 100 mesh;

[0010] Step 3: The final sintered material in step 2 is pressed into an electrolyte sheet by an isostatic press and then subjected to a third high-temperature sintering at a sintering temperature of 1200-1300°C and a heat preservation time of 40 minutes to finally obtain a finished electrolyte sheet.

[0011] In the specific technical solution,

[0012] First, because the electrolyte powder preparation temperature is high and miscellaneous products may be generated, the lithium nitride coating needs to be sintered separately (i.e., step three);

[0013] Secondly, the subsequent preparation of lithium lanthanum zirconium oxide electrolyte sheets will use higher temperatures and require a sealed environment to transform the lithium lanthanum zirconium oxide crystal from the tetragonal phase to the pure cubic phase with high ionic conductivity.

[0014] Therefore, the coating work needs to add a secondary sintering coating process in the process of electrolyte powder to electrolyte sheet. Through coating, a uniform layer of lithium nitride material can be coated on the surface of the lithium lanthanum zirconium oxide solid electrolyte. Lithium nitride can be used as a good lithium ion conductor due to its ionic conductivity of up to 10^-3S / cm. Therefore, after coating, the ionic conductivity of the lithium lanthanum zirconium oxide solid electrolyte can be greatly improved. Since lithium nitride has good stability in dry air, uniform coating can also improve the stability of the solid electrolyte in dry air, thereby reducing the cumbersome process of subsequent battery cell preparation and saving costs. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 This is a processing diagram of the present invention;

[0016] Figure 2 Fitting data for pure cubic phase. DETAILED DESCRIPTION

[0017] The following will clearly and completely describe the technical solutions in the embodiments of the present invention in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. All other embodiments obtained by ordinary technicians in this field based on the embodiments of the present invention without making any creative efforts shall fall within the scope of protection of the present invention.

[0018] It should be noted that if the embodiments of the present invention involve directional indications (such as up, down, left, right, front, back, top, bottom, inside, outside, vertical, horizontal, longitudinal, counterclockwise, clockwise, circumferential, radial, axial...), then the directional indications are only used to explain the relative position relationship, movement status, etc. between the components under a certain specific posture (as shown in the accompanying drawings). If the specific posture changes, the directional indications will also change accordingly.

[0019] In addition, if there are descriptions involving "first" or "second" in the embodiments of the present invention, the descriptions of "first" or "second" are only for descriptive purposes and cannot be understood as indicating or implying their relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" or "second" may explicitly or implicitly include at least one of such features. In addition, the technical solutions between the various embodiments can be combined with each other, but this must be based on the fact that ordinary technicians in this field can implement them. When the combination of technical solutions is contradictory or cannot be implemented, it should be deemed that such a combination of technical solutions does not exist and is not within the scope of protection required by the present invention.

[0020] like Figure 1 As shown, a coating method for improving the ionic conductivity and air stability of lithium lanthanum zirconium oxygen solid electrolyte comprises:

[0021] Step 1: Prepare M-doped lithium lanthanum zirconium oxide solid electrolyte (LLZO) by first sintering at a temperature of 900-1000°C for 6 hours. The obtained bulk material is crushed and sieved to obtain granular material with a size larger than 100 mesh, which is then placed in a polypropylene bottle for drying and storage.

[0022] The general chemical formula of the lithium lanthanum zirconium oxide solid electrolyte is: LixLa3Zr2-yMyO12, wherein 4≤x≤7, 0≤y≤0.6

[0023] Step 2: The granular material is subjected to a second low-temperature sintering to obtain a lithium nitride-coated lithium lanthanum zirconium oxide material of the M element, wherein the addition ratio of the lithium nitride is 0wt%-0.9wt%, the sintering temperature is 850-900°C, and the holding time is 4h. After the secondary coating and sintering, the lithium lanthanum zirconium oxide material of the M element coated with lithium nitride is obtained by crushing and screening 100 mesh;

[0024] Step 3: The final sintered material in step 2 is pressed into an electrolyte sheet by an isostatic press and then subjected to a third high-temperature sintering at a sintering temperature of 1200-1300°C and a heat preservation time of 40 minutes to finally obtain a finished electrolyte sheet.

[0025] First, because the electrolyte powder preparation temperature is high and miscellaneous products may be generated, the lithium nitride coating needs to be sintered separately (i.e., step 2);

[0026] Secondly, the subsequent preparation of lithium lanthanum zirconium oxide electrolyte sheets will use higher temperatures and require a sealed environment to transform the lithium lanthanum zirconium oxide crystal from the tetragonal phase to the pure cubic phase with high ionic conductivity.

[0027] Therefore, the coating work needs to add a secondary sintering coating process in the process of electrolyte powder to electrolyte sheet. Through coating, a uniform layer of lithium nitride material can be coated on the surface of the lithium lanthanum zirconium oxide solid electrolyte. Lithium nitride can be used as a good lithium ion conductor due to its ionic conductivity of up to 10^-3S / cm. Therefore, after coating, the ionic conductivity of the lithium lanthanum zirconium oxide solid electrolyte can be greatly improved. Since lithium nitride has good stability in dry air, uniform coating can also improve the stability of the solid electrolyte in dry air, thereby reducing the cumbersome process of subsequent battery cell preparation and saving costs.

[0028] The finished electrolyte sheet is tested, step 4: the finished electrolyte sheet is placed in an air atmosphere with a relative humidity of 40% for 24 to 28 hours, and then the electrolyte sheet is taken out to test its lithium carbonate content.

[0029] Testing the finished electrolyte sheet, step 5: Making blocking electrodes on both sides of the finished electrolyte sheet to test its ionic conductivity.

[0030] In a specific embodiment, the electrolyte obtained in step 3 is divided into 8 batches, numbered ①, ②, ③, ④, ⑤, ⑥, ⑦, and ⑧, wherein ① and ② have a coating ratio of 0 wt%, ③ and ④ have a coating ratio of 0.3 wt%, ⑤ and ⑥ have a coating ratio of 0.6 wt%, and ⑦ and ⑧ have a coating ratio of 0.9 wt%.

[0031] Step 4: The electrolyte obtained in step 3 is divided into 8 batches, numbered as ①, ②, ③, ④, ⑤, ⑥, ⑦, and ⑧, wherein ① and ② have a coating ratio of 0wt%, ③ and ④ have a coating ratio of 0.3wt%, ⑤ and ⑥ have a coating ratio of 0.6wt%, and ⑦ and ⑧ have a coating ratio of 0.9wt%.

[0032] Step 5: After the numbering is completed, two tests are performed: Test 1: Electrolyte sheets ①, ③, ⑤, and ⑦ are placed in an air atmosphere with a relative humidity of 40% for 24 to 28 hours, and then the electrolyte sheets are removed and tested for their lithium carbonate content; Test 2: Electrolyte sheets ②, ④, ⑥, and ⑧ are taken and their ionic conductivity is tested by making blocking electrodes on both sides of the electrolyte sheets.

[0033] Step 6: Analyze the data and draw conclusions:

[0034] The test data of the embodiment samples are as follows:

[0035] Sample number <![CDATA[Li2CO3 content (ppm)]]> Sample number Ionic conductivity (mS / cm) Sample ① 48574 Sample ② 0.087 Sample ③ 7473 Sample ④ 0.231 Sample ⑤ 4439 Sample ⑥ 0.854 Sample ⑦ 3476 Sample ⑧ 0.442

[0036] By comparing the lithium carbonate content and ion conductivity of the uncoated electrolyte sheet and the electrolyte sheets with different coating ratios, it can be seen that the ion conductivity of the coated electrolyte sheet is greatly improved, and the coated electrolyte sheet has better stability in dry air. The comparative analysis of the electrolyte sheets with different coating ratios shows that when the lithium nitride coating ratio is about 0.6wt%, both performances are achieved.

[0037] In step 3, after the third high-temperature sintering, the finished electrolyte sheet transforms from the tetragonal phase of lithium lanthanum zirconium oxide crystal to the pure cubic phase with high ionic conductivity, for example Figure 2 As shown, after refined fitting, the unit cell parameters of the Li7La3Zr2-xMyO12 (where 0≤x≤0.6) phase a=b=c≈13.03 can be calculated, so it can be judged that its phase is a pure cubic phase.

[0038] The tantalum (Ta)-doped lithium lanthanum zirconium oxide solid electrolyte (LLZO) is a lithium lanthanum zirconium tantalum oxide solid electrolyte (LLZTO).

[0039] Specifically, the lithium lanthanum zirconium tantalum oxide solid electrolyte was prepared through a hot pressing ceramic sintering process to produce an electrolyte ceramic sheet with high consistency and predetermined thickness. Its relative density was greater than 98% and its conductivity reached 0.79S cm^-1.

[0040] Specifically, when the mass fraction of the tantalum-doped lithium lanthanum zirconium oxide solid electrolyte is 50%, the room temperature ionic conductivity of the composite solid electrolyte reaches the highest value and has good compressive resistance.

[0041] Specifically, the M element is a material that does not react with lithium nitride.

[0042] This coating method can be used for other matrix materials such as sulfide electrolytes, polymer electrolytes, and other materials that do not react with lithium nitride.

[0043] Specifically, the M element is tantalum, niobium, etc.

[0044] The following are some existing methods to improve lithium lanthanum zirconium oxide solid electrolytes:

[0045] Of course, in order to achieve the structure of amorphous tantalum-doped lithium lanthanum zirconium oxide solid electrolytes: to inhibit the growth of lithium dendrites, the preparation of amorphous tantalum-doped lithium lanthanum zirconium oxide solid electrolytes, by adjusting the uniform distribution of Zr-O polyhedrons in the tantalum-doped lithium lanthanum zirconium oxide solid electrolytes or changing the ratio of elemental components to optimize lithium ion migration performance. Through these modification strategies, the comprehensive performance of LLZO solid electrolytes can be improved, promoting their application in all-solid-state batteries.

[0046] Specifically, a potassium fluoride modification layer is deposited on the surface of the lithium lanthanum zirconium tantalum oxide solid electrolyte to construct a KF / LiF electron shielding layer. In terms of interface stability, the instability of LLZO in liquid electrolytes and its interface problems with lithium metal need to be addressed through modification. For example, by depositing a potassium fluoride modification layer on the surface of LLZTO to construct a KF / LiF electron shielding layer, electrons are prevented from transferring from the current collector to the interior of the solid electrolyte, reducing the electronic conductivity of the system and inhibiting the growth of lithium dendrites.

[0047] Specifically, doping the lithium lanthanum zirconium tantalum oxide solid electrolyte with Ga3+ can suppress the H+ / Li+ replacement reaction. The air stability issue of LLZO is also a key focus of modification. Doping with Ga3+ can suppress the H+ / Li+ replacement reaction and improve the air stability of the solid electrolyte.

[0048] Specifically, the lithium lanthanum zirconium tantalum oxide solid electrolyte is composited with a modified polyionic liquid. The main aspect is mechanical properties: To improve the mechanical properties of the solid electrolyte, the researchers composited LLZO with a modified polyionic liquid to prepare a composite solid electrolyte with good flexibility and high ion transport efficiency.

[0049] The above description is only a preferred embodiment of the present invention and does not limit the patent scope of the present invention. Any equivalent structural transformation made by using the contents of the present invention specification and drawings under the inventive concept of the present invention, or directly / indirectly applied in other related technical fields, is included in the patent protection scope of the present invention.

Claims

1. A coating method for improving the ionic conductivity and air stability of lithium lanthanum zirconium oxygen solid electrolyte, characterized in that: include: Step 1: Prepare M-doped lithium lanthanum zirconium oxide solid electrolyte (LLZO) by first sintering, the sintering temperature is 900-1000°C, the insulation time is 6 hours, the obtained block material is crushed and sieved to obtain granular material with a size higher than 100 mesh, and is placed in a polypropylene bottle for drying and storage; The general chemical formula of the lithium lanthanum zirconium oxide solid electrolyte is: Li 7La3Zr2-xMyO12, wherein 0≤x≤0.6 ; Step 2: The granular material is subjected to a second low-temperature sintering to obtain a lithium nitride-coated lithium lanthanum zirconium oxide material of the M element, wherein the addition ratio of the lithium nitride is 0wt%-0.9wt%, the sintering temperature is 850-900°C, the insulation time is 4h, and after the secondary coating sintering, the lithium lanthanum zirconium oxide material of the M element coated with lithium nitride is obtained by crushing and screening 100 meshes; Step 3: The final sintered material in step 2 is pressed into an electrolyte sheet by an isostatic press and then subjected to a third high-temperature sintering. The sintering temperature is 1200-1300° C. and the insulation time is 40 minutes to finally obtain a finished electrolyte sheet.

2. The coating method for improving the ionic conductivity and air stability of lithium lanthanum zirconium oxygen solid electrolyte according to claim 1, characterized in that: Test the finished electrolyte sheets: Step 4: The finished electrolyte sheet is placed in an air atmosphere with a relative humidity of 40% for 24 to 28 hours, and then the electrolyte sheet is taken out to test its lithium carbonate content; Step 5: Make blocking electrodes on both sides of the finished electrolyte sheet to test its ionic conductivity.

3. The coating method for improving the ionic conductivity and air stability of lithium lanthanum zirconium oxygen solid electrolyte according to claim 1, characterized in that: Among them is tantalum element. In step 3, after the finished electrolyte sheet is sintered at high temperature for the third time, the lithium lanthanum zirconium oxide crystal form is transformed from a tetragonal phase to a pure cubic phase with high ionic conductivity.

4. The coating method for improving the ionic conductivity and air stability of lithium lanthanum zirconium oxygen solid electrolyte according to claim 1, characterized in that: In step 1, the M element is tantalum, and the tantalum-doped lithium lanthanum zirconium oxygen solid electrolyte is a lithium lanthanum zirconium tantalum oxide solid electrolyte.

5. The coating method for improving the ionic conductivity and air stability of lithium lanthanum zirconium oxygen solid electrolyte according to claim 4, characterized in that: Lithium lanthanum zirconium tantalum oxide solid electrolyte was prepared through hot pressing ceramic sintering process to produce electrolyte ceramic sheets with high consistency and predetermined thickness. The relative density was greater than 98% and the conductivity reached 0.79S cm^-1.

6. The coating method for improving the ionic conductivity and air stability of lithium lanthanum zirconium oxygen solid electrolyte according to claim 1, characterized in that: The M element is a material that does not react with lithium nitride.

7. The coating method for improving the ionic conductivity and air stability of lithium lanthanum zirconium oxygen solid electrolyte according to claim 6, characterized in that: The M element is tantalum or niobium.

Citation Information

Cited By

  • Preparation method of lithium lanthanum zirconium composite oxide solid electrolyte for improving air stability

    CN120864558A

  • Preparation method of halide solid electrolyte and all-solid-state lithium battery

    CN121215870A

  • Preparation method of gallium ion-doped lithium lanthanum zirconium oxide solid electrolyte

    CN121930011A